Sperm attributes and morphology on Rusa timorensis: light and scanning electron microscopy - Mahre, Mohammed Bakari; Haron, Abdul Wahid; Yusoff, Rosnina; Abdullah, Faez Firdaus Jesse; Che' Amat, Azlan; Mada, Khumran Armiya'u; Jaji, Alhaji Zubair (Elsevier, 2014)
This study provides standard information on the attributes of sperm and describes the surface structure of normal and abnormal spermatozoa of Rusa timorensis. Two fertile stags were used as the source of semen collected during the first breeding season commencing from April 5 to July 2, 2012. Another five stags were used as the source of semen collected during the second breeding season commencing from April 1 to June 27, 2013. Semen samples were collected from the stags using an electro-ejaculator. The ejaculate was processed and samples prepared for light and scanning electron microscopy (SEM) according to standard methods. No significant difference (P > 0.05) was found between sperm attributes in comparison between different stags and different months of the fertile seasons. The results of this study have also demonstrated that there are no differences in size, shape and surface structure between spermatozoa of the different stags and different months of the fertile seasons. Sperm attributes (volume, pH, sperm concentration, general motility, progressive motility and viability) were 2.2 ± 0.29 ml, 7.2 ± 0.17, 886.3 ± 39.7 × 106 spermatozoa/ml, 78.7 ± 2.01%, 80.8 ± 1.85% and 83.2 ± 0.85%, respectively. Morphological analysis showed low percentage of abnormal spermatozoa 13.9 ± 2.88%. Scanning electron microscopy revealed spermatozoa which consisted of a flat paddle-shaped head, short neck and a tail, which was subdivided into midpiece, principal piece and endpiece. The average spermatozoon was 66.2 ± 0.69 μm in total length. The flat paddle-shaped head was 7.8 ± 0.28 μm long, 4.2 ± 0.15 μm at its widest width, 2.4 ± 0.18 μm basal width and 0.7 ± 0.02 μm thick. As for the tail, the midpiece length was 13.2 ± 0.14 μm, 0.6 ± 0.04 μm in diameter; the principal piece was 42.6 ± 0.04 μm, and 2.8 ± 0.06 μm for the endpiece. Abnormal spermatozoa such as tapered head, microcephalic head, decapitated spermatozoa and bent tails were observed. Results provide standard information useful for development of strategies for semen cryopreservation and assisted reproductive technology in this species.